2019
DOI: 10.3390/microorganisms7100475
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature (15 °C) Reduces Bacterial Diversity and Prolongs the Preservation Time of Volvariella volvacea

Abstract: Straw mushroom (Volvariella volvacea) is the most commonly cultivated edible fungus in the world, but the challenges associated with the preservation have limited its marketability. Microbiology, especially bacteria, play a key role in the deterioration of food, this study aimed to reveal the succession of the bacterial community on the surfaces of V. volvacea fruit bodies under different temperature conditions. We amplified 16S rRNA genes of V4 regions, obtained the bacterial species information by using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Proteobacteria are usually classified into five groups based on rRNA sequences, which are denoted by the Greek letters α, β, γ, δ, and ε. In the present study, two classes of proteobacteria such as Alphaproteobacteria and Gammaproteobacteria were found to be more prevalent across all the samples (Figure 4), which is consistent with recent studies indicating that bacteria in this taxon are closely related to plant disease (Zhang et al, 2018;Wang et al, 2019). In the current study, the abundance of family Acetobacteraceae increased significantly both in control and 1-MCP treatment, indicating that the members in this family played an important role in fruit decay.…”
Section: Discussionsupporting
confidence: 92%
“…Proteobacteria are usually classified into five groups based on rRNA sequences, which are denoted by the Greek letters α, β, γ, δ, and ε. In the present study, two classes of proteobacteria such as Alphaproteobacteria and Gammaproteobacteria were found to be more prevalent across all the samples (Figure 4), which is consistent with recent studies indicating that bacteria in this taxon are closely related to plant disease (Zhang et al, 2018;Wang et al, 2019). In the current study, the abundance of family Acetobacteraceae increased significantly both in control and 1-MCP treatment, indicating that the members in this family played an important role in fruit decay.…”
Section: Discussionsupporting
confidence: 92%
“…No matter plants, crops or mushrooms, they would suffer from oxidative stress 24 , deficient energy 25 , and microbial attack 26 after harvest. It's reported that when plants progress into the stage of senescence, they usually initiate stress-resistant mechanism 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus is a potential pathogen that promotes decay. Previous studies have shown increased levels of Bacillus during the fermentation of pepper, and/or the storage and decay of straw mushrooms and walnuts (Wang et al, 2019;Xu et al, 2021;. Although the Bacillus subtilis, Bacillus amylolyticus, and Bacillus cereus species are the best producers of antifungal volatile organic compounds (VOCs), Bacillus species also inhibit fungal growth (Chaves-López et al, 2015) .…”
Section: Bacterial Diversitymentioning
confidence: 99%